IMF Staff papers : Volume 15 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1968)
This paper discusses how three countries in Europe-Austria, Turkey, and Finland-emerged from a prolonged inflation, restored viable economies, and resumed economic growth in the 1950s. It also attempts to draw some conclusions based on their experience as well as the experience of some other countries. In mid-1949 the Austrian Government requested assistance from the IMF in the formulation of measures that could lead the economy out of the accelerating price-wage spiral. The key issue was to find a policy mix which would lessen the burden on the budget but would help to maintain full employment. Representatives of industry agreed to the stabilization program only after they were persuaded that it was only through the program that industries could hope to maintain the prosperity that they had enjoyed in the early post-war years. They also realized that it was only thus that they could be freed of detailed government regulations which had become onerous.